Short-term hypoxia triggers ROS and SAFB mediated nuclear matrix and mRNA splicing remodeling - Chrysa Taze; Sotiria Drakouli; Martina Samiotaki; George Panayotou; George Simos; Eleni Georgatsou; Ilias Mylonis (Redox Biology, 2022)
The cellular response to hypoxia, in addition to HIF-dependent transcriptional reprogramming, also involves less characterized transcription-independent processes, such as alternative splicing of the VEGFA transcript leading to the production of the proangiogenic VEGF form. We now show that this event depends on reorganization of the splicing machinery, triggered after short-term hypoxia by ROS production and intranuclear redistribution of the nucleoskeletal proteins SAFB1/2. Exposure to low oxygen causes fast dissociation of SAFB1/2 from the nuclear matrix, which is reversible, inhibited by antioxidant treatment, and also observed under normoxia when the mitochondrial electron transport chain is blocked. This is accompanied by altered interactions between SAFB1/2 and the splicing machinery, translocation of kinase SRPK1 to the cytoplasm, and dephosphorylation of RS-splicing factors. Depletion of SAFB1/2 under normoxia phenocopies the hypoxic and ROS-mediated switch in VEGF mRNA splicing. These data suggest that ROS-dependent remodeling of the nuclear architecture can promote production of splicing variants that facilitate adaptation to hypoxia.